215k views
0 votes
I need help with this question!

I need help with this question!-example-1
User Sayboras
by
5.1k points

1 Answer

2 votes

Answer:

A = 0 -7 b= 0 -7

3 2d 3 2d

Let's calculate A and B:

  • A= 0*2d- 3*(-7) = -3*(-7) = 21
  • B= 0.2d- 3*(-7) = -3*(-7) = 21

Calculte (AB)^(-1):

  • (AB)^(-1) = (21*21)^(-1) = (21²)^(-1) = 21^(-2)

Calculte B^(-1) and A^(-1):

  • B^(-1) * A^(-1) = 21^(-1) * 21^(-1)= 21^(-1-1) = 21^(-2)

so:

(AB)^(-1) = B^(-1) * A^(-1)

User PeterX
by
4.6k points